Motivação no setor público: estudo com servidores de um centro de educação infantil localizado no município de Icapuí - Ferreira, Patrícia Sousa (Universidade Federal Rural do Semi-Árido, 2018)
The present work presents a study about the motivational situation of the municipal civil servants, who work in a Center for Early Childhood Education (CCE), located in one of the communities of the municipality of Icapuí in the State of Ceará, with reference to the theory of two factors. The main objective of this research is to understand how the process of motivation of individuals working in the public service occurs. Aiming to reach the same, a qualitative research was carried out, using the interview as a tool for data collection, later the data were transcribed, arranged in categories and finally analyzed through interpretative analysis. In front of the obtained results the hygienic factors that are present, positively affecting the performance are: the salary, the relationship with the team and with the management and stability. While among the three motivational factors analyzed, only the achievement factor is causing motivation among the servers of the CCE researched and the others are blocking it.
Keywords: Centro de Educação Infantil; Servidor público; Motivação; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO